2003
DOI: 10.1080/01926230390183661
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Mustard-Induced Apoptosis in Hairless Guinea Pig Skin

Abstract: The present study was aimed to examine whether apoptosis is involved in the pathogenesis of sulfur mustard (SM)-induced basal cell death. Skin sites of the hairless guinea pig exposed to SM vapor for 8 minutes were harvested at 3, 6, 12, 24, and 48 hours postexposure. Immunohistochemical detection of basal cell apoptosis was performed using the ApopTag in situ apoptosis labeling kit. Only occasional apoptotic basal cells (BC) were observed in nonexposed and perilesional control sites. At lesional sites, apopto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Studies supporting the induction of apoptosis following SM exposure to cultured cells and whole skin have identified characteristic apoptotic features, including increases in p53, reduction in Bcl-2 levels, nucleosomal DNA fragmentation, PARP cleavage, and caspase activation [24,25,27,45,46]. In the present study, microarray analysis has identified gene transcripts at all six SM doses that are associated with apoptosis, including retinoic acid receptor beta (RAR␤), TNF receptor superfamily ligands, and cyclin G. The role of both retinoic acid receptors and TNF receptor ligands in apoptosis has been studied extensively [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies supporting the induction of apoptosis following SM exposure to cultured cells and whole skin have identified characteristic apoptotic features, including increases in p53, reduction in Bcl-2 levels, nucleosomal DNA fragmentation, PARP cleavage, and caspase activation [24,25,27,45,46]. In the present study, microarray analysis has identified gene transcripts at all six SM doses that are associated with apoptosis, including retinoic acid receptor beta (RAR␤), TNF receptor superfamily ligands, and cyclin G. The role of both retinoic acid receptors and TNF receptor ligands in apoptosis has been studied extensively [47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular shrinkage, cytoplasmic budding, nuclear fragmentation, and apoptotic bodies are pathognomonic of apoptosis. Confirmation by transmission electron microscopy of cytoplasmic budding bearing nuclear fragments is essential in the differential diagnosis of cellular apoptosis (Kan et al, 2003). Apoptosis contributes to the mechanisms of removal of unwanted cells in normal physiological processes (e.g., during organ development, sloughing of the endometrium in early menstruation period, immune response, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Maruziyet sonrası derideki tipik belirtilerdeneritem ve blister oluşumunun neden olduğu gerginlik rahatsızlık verici düzeydedir. Bül oluşumu dermis ile epidermis tabakalarını bir arada tutan protein bağların harabiyetisonrasında ortaya çıkar ve maruziyetten bir gün sonra belirgin hale gelir (34,35). Bununla birlikte ortaya çıkan şiddetli kaşıntı, derideki yanmaya bağlı olarak oluşan büller sonrası azalır.…”
Section: Nitrojen Mustard (Terapötik Kullanım);unclassified